Acceptability of COVID-19 vaccination in Herat, Afghanistan - Don Eliseo Lucero-Prisno III; Ahmad Neyazi; Attaullah Ahmadi; Omid Tabesh; Habibah Afzali; Kenesh Dzhusupov; Md Shariful Islam; Rayan Rachmad Nugraha; Blaise Ntacyabukura; Shyam Sundar Budhathoki; Lin Xu; Wahid Majrooh (Razi International Medical Journal, 2021)
Background: COVID-19 vaccine hesitancy is one of the major concerns in the roll out of vaccines in many countries. The aim of the study was to assess the level of COVID-19 vaccine acceptability among the population in Herat, Afghanistan, the third largest city in the country.